HOUSES AS EXCURSION OBJECTS FOR THE ORGANIZATION OF TOURIST TRIPS IN UKRAINE - HABA, Myroslava; LUCHYSHYN, Nadia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines houses as excursion objects for the organization of tourist trips in Ukraine, which will contribute to the attraction of new travelers. It was found that the study of houses as possible potential excursion objects for the organization of tourist trips in Ukraine will contribute to the attraction of new travelers, the expansion of the range of tourist objects and the satisfaction of their specific requests, which in turn will give an opportunity to increase the potential of little-known tourist regions and make a profit. in particular, in modern conditions. It was found that nowadays interesting and unusual buildings can play a big role in the organization of tourist trips. Excursion objects can be buildings and structures, memorial monuments related to the life and activities of outstanding personalities, masterpieces of architecture and urban planning, residential and public buildings, buildings of industrial enterprises, engineering structures, buildings of cultural and religious purpose, fortifications and other buildings.There are many interesting and unusual buildings in Ukraine that can be used as objects of tourist display in tours, which will make it possible to expand the range of offers and satisfy the specific requests of potential tourists. Most often, these are restaurants and museums that are specially built to attract customers and tourists. However, no less interesting tourist facilities, in addition to the above, which can attract new tourists to Ukraine, are also public and private houses, which are memorable for their unusual architecture. Therefore, the most unusual buildings built in Ukraine were chosen for the study, which will contribute to increasing interest in such objects among consumers and in their further use in the organization of tourist trips when choosing display objects. It was determined that the most unusual structures are houses in Ukraine, which can be included as objects of tourist display in the organization of tourist trips.
Keywords: houses; tourism; construction; unusual structures; tourist trips